PENGARUH LAPORAN KEUANGAN TERHADAP KINERJA KEUANGAN BADAN PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN PINRANG - Hamdayani, Hamdayani; Yusran Bachtiar (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of financial statements on the financial performance of regional financial management agencies in Pinrang Regency. The data collection techniques used in this study were observation and questionnaires. The sample in this study amounted to 66 ASN employees. The data analysis technique used in this research is using simple regression analysis. The results of this study found that financial statements have a significant effect on financial performance. The results of this study also show that the R Square value is 0.760 which explains that in this regression model the ability of financial statements to explain financial performance is 76.0% and the remaining 24% is explained by other variables. The results of the regression equation in this study were 0.810. The results of the regression coefficient of 81.4%. And for hypothesis testing (β 0) then the partial test results in this study are (β = 0.981) for the financial statement variable with a significant 0.00, this result states that the financial statements have a significant effect on financial performance.